Development of Phenol Red Colorimetric RT-LAMP Assay in High-Buffered SARS-CoV-2 Sample - Putera Rakhmat; Uus Saepuloh; Huda Shalahuddin Darusman (HAYATI Journal of Biosciences, 2023)
Colorimetric RT-LAMP Assay is a diagnostic method that has attracted much attention because of its rapidity, simplicity, and accuracy compared to other disease diagnosis methods. Despite having many advantages, the RT-LAMP Colorimetric Assay has disadvantages, especially for kits that use phenol red as an indicator. The disadvantage derives from the input RNA/DNA samples containing high buffer levels, which causes no color change and false-negative results. This study aimed to develop and optimize the colorimetric RT-LAMP method on high-buffered SARS-CoV-2 RNA samples. We found that a temperature of 69°C for 50 minutes with the addition of post-treatment in the form of heating at 80°C for 10 minutes is an optimal condition for high-buffered SARS-CoV-2 samples. The condition proved effective in changing the result's color from red (negative) to yellow (positive). We also classified the analysis results based on the correlation between the Cycle threshold (Ct) value of SARS-CoV-2 viruses and the Optical Density (OD) value, which was quantified using a spectrophotometer at 415 nm (with a correlation value of -0.9084), where yellow color indicated Ct below 20, amber color indicated Ct between 20 and 30, orange color indicated Ct between 30 and 35, and red indicated Ct more than 35 (negative). In conclusion, this study successfully detects the SARS-CoV-2 virus in high-buffered samples using Phenol Red Colorimetric RT-LAMP Assay, with a sensitivity of 85% for Ct Cutoff 40.